2021
DOI: 10.3390/ijms22136641
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Metabolic Profiling of High-Temperature Treated Storage Roots Reveals the Mechanism of Saccharification in Sweetpotato (Ipomoea batatas (L.) Lam.)

Abstract: The saccharification of sweetpotato storage roots is a common phenomenon in the cooking process, which determines the edible quality of table use sweetpotato. In the present study, two high saccharified sweetpotato cultivars (Y25, Z13) and one low saccharified cultivar (X27) in two growth periods (S1, S2) were selected as materials to reveal the molecular mechanism of sweetpotato saccharification treated at high temperature by transcriptome sequencing and non-targeted metabolome determination. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The raw eating quality of tubers and root crops requires different evaluations. The heating process of tuberous roots affects the starch gradually gelatinizing, leading to the leaching of maltose [13]. Then, the sugar content of sweet potato increases and increases the risk associated with sweet potato consumption for diabetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The raw eating quality of tubers and root crops requires different evaluations. The heating process of tuberous roots affects the starch gradually gelatinizing, leading to the leaching of maltose [13]. Then, the sugar content of sweet potato increases and increases the risk associated with sweet potato consumption for diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…Raw sweet potatoes have less maltose sugar than those that have undergone heat processing because heating affects the starch's transformation into maltose [12]. Cooked sweet potatoes are higher in sugar, as the heat turns starches into maltose for easier digestion, providing a sweeter flavor than raw sweet potatoes [13]. More sugar increases blood sugar after eating, causing concerns about blood pressure and diabetes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that phenolic acids form complexes with the active sites of enzymes through hydrogen bonding and hydrophobic interaction, thus blocking the active sites of enzymes or changing the conformation of enzymes, resulting in a decrease in their catalytic activity. 34,35 Our previous study demonstrated that total polyphenol was significantly elevated after fermentation in LFBE, and that LFBE played a significant role in alleviating obesity and type 2 diabetes in rats caused by a high-fat diet, which indicated that L. p dy-1 fermentation could improve the physiological activity of phenolic acid, especially in the glucose and lipid metabolism. 13 The improvement in the physiological activity due to phenolic acid may be related to the key role of esterase secreted during barley fermentation.…”
Section: Papermentioning
confidence: 99%
“…To date, multi-omics studies in sweetpotato are limited. In two recent studies, integration of transcriptomic and metabolomic data facilitated the identification of genes and metabolites involved in anthocyanin accumulation and the mechanism of saccharification in tuberous roots of sweetpotato ( He et al., 2020 ; Li et al., 2021a ). Genome-wide analysis of expression QTLs (eQTLs) has also been applied to sweetpotato and was used to reveal the regulatory architecture of gene expression variation ( Zhang et al., 2020a ; Chen et al., 2021 ).…”
Section: Progress In Sweetpotato Breedingmentioning
confidence: 99%